Development and Validation of a Competency Self-Assessment Tool for The Nurse Interns - Nema F. Saad; Hanaa M. Abd Rabou (Evidence-Based Nursing Research)
Contents: Nurse Interns need more attention to their self-confidence and self-assessment abilities. Self-assessment is an essential approach for testing their knowledge, skills, and attitudes.